Preconception Mental Health, Socioeconomic Status, and Pregnancy Outcomes in Primiparous Women - Satu-Maarit Björkstedt; Satu-Maarit Björkstedt; Hannu Koponen; Hannu Kautiainen; Hannu Kautiainen; Mika Gissler; Mika Gissler; Pirjo Pennanen; Johan G. Eriksson; Johan G. Eriksson; Johan G. Eriksson; Johan G. Eriksson; et al. (Frontiers in Public Health, 2022)
Background:One in four women of childbearing age has some degree of mental disorders and are, therefore, prone to both pregnancy complications and adverse health outcomes in their offspring. We aimed to evaluate the impact of preconception severe mental disorders on pregnancy outcomes in primiparous women.MethodsThe study cohort was composed of 6,189 Finnish primiparous women without previously diagnosed diabetes, who delivered between 2009 and 2015, living in the city of Vantaa, Finland. Women were classified to have a preconception severe mental disorder if they had one or more outpatient visits to a psychiatrist or hospitalization with a psychiatric diagnosis 1 year before conception. Data on pregnancies, diagnoses, and pregnancy outcomes were obtained from national registers at an individual level.ResultsPrimiparous women with preconception severe psychiatric diagnosis were younger, more often living alone, smokers, and had lower educational attainment and lower taxable income than women without psychiatric diagnosis (for all p < 0.001). Of all women, 3.4% had at least one psychiatric diagnosis. The most common psychiatric diagnoses were depression and anxiety disorders. The most common comorbidity was the combination of depression and anxiety disorders. There were no differences in the need for respiratory treatments, admissions to the neonatal intensive care unit, or antibiotic treatments between the offspring's groups.ConclusionAlthough primiparous women had severe mental disorders, the well-being of newborns was good. The most common severe mental health disorders were depression and anxiety disorders, and psychiatric comorbidity was common. Women with severe mental disorders more often belonged to lower socioeconomic groups.